Mild hyperthermia (39°C) attenuates berberine chloride cytotoxicity against osteosarcoma cells - Mohammed Ali Nashiry,; Alyaa Rajih Al-Khateeb,; Aisha Mohd Din,; Norita Salim,; Aletza Mohd Ismail,; Yeap, Swee Keong; Gabriele Ruth Froemming, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Many studies reported that antioxidants and dietary supplements increase tumour progress and reduce survival. Hyperthermia is an adjuvant treatment to sensitise cancer cells for radio- or chemotherapy. The current study was carried out to determine the effects of berberine chloride and hyperthermia on bone cancer cells. MG-63 osteosarcoma cells were treated with hyperthermia (39, 43 and 45°C, respectively) for 1 h. Then, the cells were treated with a low toxic dose of berberine chloride (80 μg/mL). After that, all treated groups were recovered at 37°C for 24 h. Finally, all groups were treated with hyperthermia (39, 43 and 45°C) for the second time (1 h) and were recovered for 3 h at 37°C. Cells exposed to hyperthermia without treatment of berberine chloride were used as hyperthermia control. Cells treated with 80 μg/mL of berberine at 37°C served as berberine control and cells incubated at 37°C were used as an untreated control. All treated groups showed significant apoptosis compared to the control group (p<0.05) except 39°C. On the other hand, mild hyperthermia treatment (39°C) resulted in a reduction of berberine-induced apoptosis (p<0.001). Severe and moderate hyperthermia did not show a significant increase in the rate of apoptosis compared to berberine treated cells. Mild hyperthermia treatment can effectively reduce berberine cytotoxicity and implying negative effects on cancer therapy.